IMPLEMENTASI METODE TALAQQI DALAM MENGHAFAL AL-QUR’AN PADA ASRAMA PUTRI MADRASAH ALIYAH NEGERI 2 SURAKARTA - Rusmiyaty, Siti; Suhadi, S; Ulfah, Yetty Faridatul (MAMBA'UL 'ULUM, 2025)
The purpose of this research is to find out the implementation of the Talaqqi method in memorizing the Qur'an. This research used descriptive qualitative research method. Data were collected through observation, interviews, and documentation. The Miles and Huberman model analysis technique was used to analyze the data collected, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that 1) the implementation of the talaqqi method is divided into three stages, of which the first stage is the initial stage and the second stage is the core stage of halaqoh, and the last is the closing and evaluation stage; 2) Supporting factors and inhibiting factors for the implementation of the talaqqi method in memorizing the Qur'an are divided into two factors, namely internal factors and external factors. Internal factors include interest in memorizing the Qur'an and self-motivation, while external factors include motivation from ustadzah and parents and a supportive learning environment.